Rekonstruksi bentuk lambung kapal dalam format tiga dimensi (3D) dengan teknik fotogrametri - Evander Nelwan; Kawilarang W. A. Masengi; Vivanda O. J. Modaso; Alfred Luasunaung; Johnny Budiman; Fanny Silooy; Revols D. CH. Pamikiran (Universitas Sam Ratulangi, 2024)
Fishing boat has unique characteristics, such as seaworthiness, maneuvering, boat’s velocity, displacement, fishing gear layout, and catch storage facilities. With increasing development of photographic technology, photography is not merely an art but it has become a field of mathematics, making it a technique that can be integrated with software technology designed to produce digital data objects in the form of 3D images called Photogrammetric technique. This study is to obtain the reconstruction of the boat's hull based on the Photogrammetric software, to determine the effect of photography to obtain a 3D image, and to know the weakness and strength of 3D reconstruction of the boat’s hull. The images in this study were obtained using a POCO F3 smartphone camera integrated with the PIX4Dcatch application and analyzed with Agisoft Metashape Professional (Trial Version). From this research, we concluded that 1) the reconstruction of the boat hull can be obtained by using Photogrammetric techniques in the PIX4Dcatch application followed by the Agisoft Metashape Professional (Trial Ver.) software analysis; 2). With photographic equipment and several data processing software, the boat’s shape could be produced in 3D images, and 3). There are several advantages in reconstructing the ship's hull with the Photogrammetric technique, namely producing the ship's reconstruction of 3D images, obtaining the principal dimensions of the boat, such as the area and volume of the boat, that could be as the basic data for boat resistance and ship stability calculation, and the work could be done by one person only.